Osimertinib in the treatment of resected EGFR-mutated non-small cell lung cancer: a cost-effectiveness analysis in the United States - Huo, Gengwei; Song, Ying; Liu, Wenjie; Cao, Xuchen; Chen, Peng (Frontiers in Pharmacology, 2024)
Background: In the double-blind phase III ADAURA randomized clinical trial, adjuvant osimertinib showed a substantial overall survival benefit in patients with stage IB to IIIA, EGFR-mutated, completely resected non-small cell lung cancer (NSCLC). We conduct a cost-effectiveness analysis comparing the use of adjuvant osimertinib to placebo in patients with stage IB to IIIA, EGFR-mutated, resected NSCLC. Methods: Based on the results obtained from the ADAURA trial, a Markov model with three-state was employed to simulate patients who were administered either osimertinib or placebo until disease recurrence or completion of the study period (3 years). Quality-adjusted life-years (QALYs), lifetime costs, and incremental cost-effectiveness ratio (ICER) were calculated with a willingness-to-pay (WTP) threshold of 150,000 per QALY. Both univariate and probabilistic sensitivity analyses were carried out to explore the robustness of the model. Results: Osimertinib produced additional 1.59 QALYs with additional costs of 492,710 compared to placebo, giving rise to ICERs of 309,962.66/QALY. The results of the univariate sensitivity analysis indicated that the utility of disease-free survival (DFS), cost of osimertinib, and discount rate had the greatest impact on the outcomes. Probabilistic sensitivity analysis showed that osimertinib exhibited a 0% chance of being considered cost-effective for patients using a WTP threshold 150,000/QALY. Conclusion: In our model, osimertinib was unlikely to be cost-effective compared to placebo for stage IB to IIIA, EGFR-mutated, completely resected NSCLC patients from the perspective of a U.S. payer at a WTP threshold of 150,000 per QALY.